The Cyberith Virtualizer - Cakmak, Tuncay (International Journal of Virtual Reality, 2015)
This device developed by the young virtual-reality-enthusiasts of "Cyberith" is a locomotion device that delivers completely new impressions and experiences regarding gameplay and entertainment